Media Strategy For Umkm Ecoprint Product Promotion Sekar Widuri In Mojosari - Adjuar, Hendro; Winarno, Winarno; Anggapuspa, Meirina Lani; Ardani, Muhammad Widyan (Proceeding of International Joint Conference on UNESA, 2024)
UMKM Sekar Widuri was founded on December 15, 2021 by Imsyak Alifah. UMKM Sekar Widuri provides ecoprint training to PKK group mothers in Seduri Mojosari village. Limited knowledge about promotional media strategies from ecoprint products that have been produced affects sales and the difficulty of competing with other ecoprint products. Because it only uses makeshift promotional media without a logo, less attractive packaging forms, without any labels on the products produced, posters, signboards and social media. So that the results of ecoprint products offered are limited to certain circles. Therefore, it is necessary to increase knowledge not only in terms of ecoprint techniques but also in terms of marketing media strategies so that they can be known by the wider community and have a high selling value. The main output is in the form of logos, unique and attractive packaging, other supporting promotional media such as posters, flyers, signboards, and hang tags. The activities carried out by the proposer team with partners are as follows: 1) Feasibility Study in the form of a preliminary study conducted by the proposer team to find out the problems experienced by Sekar Widuri UMKM in participating in the activities offered, judging from the problems faced. 2) The implementation of activities begins with a licensing process of both places and facilities with Sekar Widuri UMKM in Seduri village to ensure the time and place of implementation. Tracking with technique: presentation. 3) After the activity after the implementation of the activity, the Team prepares a final report which will be presented through an International seminar (ICCSAL). After that, the team also compiled articles to be published in scientific journals/proceedings